Compartment transfers and shareholder value: A long-term event study on NYSE Euronext Paris - Hichem, Ghnimi (Financial Risk and Management Reviews, 2025)
This paper investigates the impact of market compartment transfers on the long-term performance of French firms listed on NYSE Euronext Paris. This study employs a long-term event study methodology on a sample of 84 French companies that announced a compartment transfer on NYSE Euronext Paris between 2000 and 2019. The results indicate that firms announcing a compartment transfer exhibit excess returns below those predicted by the asset pricing model, reflecting weaker risk-adjusted performance and suggesting that such transfers do not create shareholder value. The findings provide insights for investors and regulators into the limited long-term benefits of listing transfers and how markets process information in segmented trading environments.